Health-associated changes of the fecal microbiota in dairy heifer calves during the pre-weaning period - Scully, Sabine; Earley, Bernadette; Smith, Paul E.; McAloon, Catherine; Waters, Sinéad M. (Frontiers in Microbiology, 2024)
Neonatal calf diarrhea is a multifactorial condition that occurs in early life when calves are particularly susceptible to enteric infection and dysbiosis of the gut microbiome. Good calf health is dependent on successful passive transfer of immunity from the dam via colostrum. There are limited studies on the developing gut microbiota from birth to weaning in calves. Therefore, the study objective was to examine the effect of immune status and diarrheal incidence on the development of the fecal microbiota in Jersey (n=22) and Holstein (n=29) heifer calves throughout the pre-weaning period. Calves were hand fed a colostrum volume equivalent to 8.5% of their birthweight, from either the calf's dam (n=28) or re-heated mixed colostrum (≤2 cows, ≤1d; n=23) within 2 h of birth. All calves were clinically assessed using a modified Wisconsin-Madison calf health scoring system and rectal temperature at day (d) 0, d7, d21 or disease manifestation (DM) and weaning (d83). Weights were recorded at d0, d21 and d83. Calf bloods were collected at d7 for calf serum IgG (sIgG) determination. Fecal samples were obtained at d7, d21/DM (mean d22 (SE 0.70)) and at weaning for 16S rRNA amplicon sequencing of the fecal microbiota. Data were processed in R using DADA2; taxonomy was assigned using the SILVA database, and further analyzed using Phyloseq and MaAsLin 2. Significant amplicon sequence variants (ASVs) and calf performance data underwent a Spearman rank-order correlation test. There was no effect (P>0.05) of colostrum source or calf breed on serum total protein. An effect of calf breed (P<0.05) was observed on sIgG concentrations in that Holstein calves had 6.49 (SE 2.99) mg/mL higher sIgG than Jersey calves. Colostrum source and calf breed had no effect (P> 0.05) on health status or on the α-diversity of the fecal microbiota. There was a health status × time interaction (P< 0.001) whereby α-diversity increased with time, however diarrheic calves had reduced microbial diversity at DM. No difference (P> 0.05) in β-diversity of the microbiota was detected at d7 or d83. At the genus level, 33 ASVs were associated (adj.P< 0.05) with health status over the pre-weaning period.